TINJAUAN HAK ASASI MANUSIA DALAM PENERAPAN SANKSI KEBIRI KIMIA BAGI PELAKU KEKERASAN SEKSUAL TERHADAP ANAK - Alvira Damayanti; Amelia Elisabeth Putri Kusuma; Lambertus Josua Tallaut; Ade Adhari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Sexual violence that occurs by involving children as victim, is increasingly happening, encouraging the government to be more serious in dealing with this crime. The government imposes chemical castration sanctions for perpetrators of sexual vionelce against children. The chemical castration sanction policy received pro and contra responses in society, one of the reason why chemical castration sanctions could not be enforced was because it violated human rights, thus raising questions about the application of chemical castration sanctions for perpetrators of sexual violence against children from a human rights perspective. The purpose of this study was to identify and understand the review of human rights in the application of chemical castration sanctions for perpetrators of sexual vionelce against children. This type of research uses normative legal research methods by collecting secondary data and using a legal approach which is then analyzed using data analysis techniques with deductive methods. Chemical castration sanctions as additional punishment can be imposed on perpetrators who have been covicted for committing a similar crime, namely sexual violence against children or recidives and causing more than 1 (one) victim, causing serious inury, mental disorders, infectious diseases, disturbed or loss of reproductive function, or the victim dies. Chemical castration is an unconstitutional act because it is against the state constitution and violates human right. The application of castration sanctions for perpetrators of sexual violence against children has not been proven effective in reducing the number of sexual violence against children.